Analiza osnovnošolskih šol v naravi s plavalnimi vsebinami - Drevenšek, Matej (Šport (Ljubljana), 2019)
The purpose of this study was to analyze information on the implemented Schools in nature that include swimming activities. The sample of the survey included all (n=452) Slovenian central primary schools in school year 2016/2017. Only the schools (n=333) that organized the Schools in nature with swimming contents and had their data published on their websites were analyzed in detail. Since some schools organized more than one program in the same year, the total of 352 Schools in nature were included in the survey. There were statistically significant differences in the number of Schools in nature with swimming activities regarding to the size of the school and the statistical region. Most often, schools organized five-day Schools in nature that included swimming activities (83.3%), Schools in nature were organized in June and September (68.4%), and involved the 5th grade pupils (54.3%). Most of the Schools in nature were organized at seaside (77%), along Slovenian coast (62.7%), with the city of Ankaran as the most common destination (19.9%).
Keywords: dolžina; location; lokacija; osnovna šola; outdoor activities; plavanje; primary school; school in nature; spletne strani; sport; swimming; šola v naravi; šport; učenci; website